Greenhouse Gas Emissions, Energy Consumption and Economic Growth: Empirical Evidence from Gulf Cooperation Council Countries - Saqib, Najia (International Journal of Energy Economics and Policy, 2018)
This paper examines the relationship between GHG emissions, energy consumption and economic growth with panel data of the six Gulf Cooperation Council (GCC) countries—Saudi Arabia, Kuwait, United Arab Emirates, Qatar, Bahrain, and Oman over the period 1996-2017. This study empirical results show that exists of bidirectional causal relationship between energy consumption and economic growth. However, the results support the occurrence of unidirectional causality from energy consumption to GHG emissions without any feedback effects, and there exists bidirectional causal relationship between economic growth and GHG emissions for the region as a whole. The study suggests that environmental and energy policies should recognize the differences in the relationship between energy consumption and economic growth in order to maintain sustainable economic growth in GCC region. Keywords: Environmental Kuznets Curve, Environmental degradation, energy consumption, economic growth JEL Classifications: N50, Q00, O13, O47 DOI: https://doi.org/10.32479/ijeep.7269